KREDIBILITAS PENYIAR JEJE RADIO 105.1 FM SURABAYA DALAM PROGRAM MARATHON HITS MALAM - Ramadhan, Zulfikar Yufi; Maruta, IGN. Anom; Satvikadewi, AAI. Prihandari (representamen, 2017)
Jeje Radio has some fresh and hits programs, one of them is a Marathon Hits Night which isbroadcasted from 19.00 – 23.00 pm. The concept of this program certainly brings the broadcaster tobe a high credibility person. In this study were selected 3 Marathon Hits Malam programbroadcasters in Jeje Radio Surabaya, among other Deli Aldiano, Imah Cinara, and Widi Ariyani. Theresults of this analysis show that Widi Ariyani is the broadcaster meets criteria for Derived andTerminal Credibility. She has most credible in term of experience, education, and attitude. While,Imah Cinara is the broadcaster who goes into all categories credibility but she is not really measureenough. Apart from that, the listeners have the Latitude of Acceptance because they have a flexibleassessment against the broadcast pattern Ima Cinara. The potential of each broadcaster will increaseby company support. Therefore, supporting facilities are necessary to be given to improve their abilityand quality.Keywords : Jeje Radio Surabaya, Broadcaster of Marathon hits malam, credibility